Exploring the Impact of Product Quality, Performance, Consumer Experience, Positive eWOM on Purchase Intention and Sustainability: On Consumer Railways - Sonny Indrajaya; Tukhas Shilul Imaroh; Dewi Nusraningrum (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2025)
Background: Developing an analysis model regarding product quality, performance, consumer experience, positive eWOM, where the proposed model is in accordance with the theory of purchase intention and sustainability of trains, where passengers in Jakarta are the target objects, using demographic factors such as gender, age, country of origin. Purpose: Analysis of consumer responses to the situation and conditions existing in the railways and whether the railways can be sustainability. Method: A quantitative approach was used in this study with an online survey conducted using Google Forms and a structured questionnaire survey conducted on 225 Indonesian and foreign respondents selected based on purposive sampling. Data analysis used SEM PLS, to determine the impact of the relationship on purchase intentions and sustainability. Findings: Shows that attachment exists and has a strong influence and impact on purchase intention and business sustainability. The implications are in terms of passenger experience, both in terms of service and comfort, as well as the sustainability of trains in Indonesia. Conclusion: Improvement of product quality, performance, consumer experience, positive eWOM can increase purchase intention. Increased purchase intention can increase the sustainability of customer relationships. Research limitations: The new analysis focuses on aspects related to the variables of product quality, performance, consumer experience, positive ewom, purchase intention, sustainability trains. New response characteristics involving gender, division, continent, data analysis techniques, used, in this study are limited to quantitative methods. Research implications: This study provides conditions and situations regarding trains related to product quality, performance, consumer experience, positive ewom, purchase intention, railway sustainability.